Analysis of students understanding mathematics concept based on resolving HOTS questions at SMP Negeri 1 Gambut - Rolina Amriyanti Ferita; Williza Yanti; Bella Santika (STKIP PGRI Banjarmasin, 2022)
This study aims to analyze the ability to understand mathematical concepts based on the theory of Kilpatrick et al., of class VIII SMP Negeri 1 Gambut during the pandemic related to solving the Higher Order Thinking Skill (HOTS) on the material of Two Variable Linear Equation System. According to the joint decision of the Minister of Education and Culture, Minister of Religion, Minister of Health, and Minister of Home Affair regarding guidelines for implementing learning during the Pandemic Coronavirus Disease 2019 (Covid-19) with this research can be carried out offline. The type of research used is qualitative research. The research subjects were 18 students of class VIII SMP Negeri 1 Gambut. The instrument used is a test of students’ mathematical understanding abilities on HOTS questions and interview sheets. In the stage of solving the problem, some student carry out the process of the correct steps but are still not optimal in completing the answer. There are also many students who do not understand the indicators of planning problem solving and many students who carry out a settlement plan but are still wrong in working on the problem. Based on the results of the study, it can be concluded that the ability to understand students’ mathematical concepts based on solving the Higher Order Thinking Skill (HOTS) questions at SMP Negeri 1 Gambut on SPLDV material is still low, especially in understanding the problem, activities to design problem-solving strategies, activities to perform calculations, and activities to re-examine the results or solutions.